HR practices of a transformational corporate culture (construction to hospitality service) and challenges to retain employees in a new work environment: an analysis on Cityscape International Ltd. - Rownok, Shusmita (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.